2022
DOI: 10.3389/fmolb.2022.907452
|View full text |Cite
|
Sign up to set email alerts
|

Present Impact of AlphaFold2 Revolution on Structural Biology, and an Illustration With the Structure Prediction of the Bacteriophage J-1 Host Adhesion Device

Abstract: In 2021, the release of AlphaFold2 - the DeepMind’s machine-learning protein structure prediction program - revolutionized structural biology. Results of the CASP14 contest were an immense surprise as AlphaFold2 successfully predicted 3D structures of nearly all submitted protein sequences. The AlphaFold2 craze has rapidly spread the life science community since structural biologists as well as untrained biologists have now the possibility to obtain high-confidence protein structures. This revolution is openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
(48 reference statements)
1
16
0
Order By: Relevance
“…The Dit proteins analyzed in this study all form a core assembling the belt and galectin domains, similar to that observed for other phage Dits (Sciara et al, 2010;Veesler et al, 2010;Veesler et al, 2012) [or an OB-fold in phage T5 (Flayhan et al, 2014)]. Moreover, the Dits' CBMs exhibit similar folds for the five phages, whose the closest structure in the PDB is that of one of the two CBMs belonging to the Dit of L. casei phage J-1 (Dieterle et al, 2017;Goulet, 2022).…”
Section: Discussionsupporting
confidence: 82%
“…The Dit proteins analyzed in this study all form a core assembling the belt and galectin domains, similar to that observed for other phage Dits (Sciara et al, 2010;Veesler et al, 2010;Veesler et al, 2012) [or an OB-fold in phage T5 (Flayhan et al, 2014)]. Moreover, the Dits' CBMs exhibit similar folds for the five phages, whose the closest structure in the PDB is that of one of the two CBMs belonging to the Dit of L. casei phage J-1 (Dieterle et al, 2017;Goulet, 2022).…”
Section: Discussionsupporting
confidence: 82%
“…AF2 structural predictions are a potent and fast tool to determine the structure–function relationships of viral replication/translation machineries. Precisely knowing domain boundaries is highly valuable to recombinantly produce stable and active proteins and perform structural and functional analyses [ 32 ]. In particular, predicted structures can be used as templates to design mutants and test their activity, or to design inhibitors of the replication machineries, which is a target of choice for efficient antiviral treatments as illustrated by the NS5B-RdRp inhibitor used to treat HCV-infected patients [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is well adapted to predict structures of long, flexible and multi-domain proteins that cannot be analyzed as a whole using experimental approaches such as X-ray crystallography and electron microscopy. Recently, we applied this method to bacterial viruses (bacteriophages) to determine the structures of their whole host-binding machineries with several multi-domain proteins [ 31 , 32 ]. Moreover, as compared with homology modeling, AF2 produces structures that do not suffer from sequence bias, with an estimate of the prediction reliability for each protein residue given by a confidence score, the predicted local distance difference test (pLDDT, from 0 to 100).…”
Section: Introductionmentioning
confidence: 99%
“…30,31 AF2 models therefore have a considerable impact on structure determination by X-ray crystallography and NMR. 23,29,32,33 Furthermore, the observation that AF2/RF models can be used for molecular replacement while other models cannot, suggests that we might question our definition of what a good model is. Indeed, some models that could have been defined as good by many metrics were not accurate enough for molecular replacement.…”
Section: Pipelinesmentioning
confidence: 99%